Conventional lymphangiography (CL) in the management of postoperative lymphatic leakage (PLL): a systematic review = Konventionelle Lymphangiografie (KL) beim Management postoperativer Lymphleckagen (PLL) - Sommer, Christof-Matthias; Pieper, Claus Christian; Itkin, Maxim; Nadolski, Gregory J.; Hur, Saebeom; Kim, Jinoo; Maleux, Geert; Kauczor, Hans-Ulrich; Richter, Goetz M. (RöFo, 2020)
BACKGROUND: Postoperative lymphatic leakage (PLL) is usually managed by conservative and/or surgical treatments but these procedures can be challenging to perform and potentially clinically ineffective. Therefore, conventional lymphangiography (CL) has emerged as an important alternative. The aim of this review is to present the available outcome data on CL in the management of PLL. - METHOD: A systematic literature search (PubMed) using the MeSH term "lymphangiography" was performed and the search was restricted to literature published between January 2007 and August 2019. Identification, screening, and assessment for eligibility and inclusion were conducted in accordance with PRISMA. - RESULTS: From the initially obtained 1006 articles (identification), 28 articles with a total of 201 patients were finally included (inclusion). The methodological quality of all included articles corresponds to level 4 (Oxford Centre for Evidence-based Medicine - Levels of Evidence, March 2009). PLL occurs after oncological and non-oncological surgery in the form of chylothorax, chylous ascites, and cervical, thoracic, abdominal and peripheral lymph fistula and/or lymphocele. The technical success rate of CL is 75-100%. Access for CL is transpedal (176 patients) or intranodal (25 patients). Lipiodol is used as the contrast material in all articles, with a maximum amount of 20ml for transpedal CL and 30ml for intranodal CL. The X-ray imaging modalities used for CL are fluoroscopy, radiography and/or CT. Two articles report CL-associated major complications and CL-associated morbidity and mortality. The PLL cure rate is 51-70% for transpedal CL (time to PLL cure: 2-29 days) and 33-100% for intranodal CL (time to PLL cure: 2-<30 days). Bailout procedures in the case of clinically ineffective CL include a range of treatments. - CONCLUSION: CL is feasible, safe, and effective in the management of PLL. Lipiodol as the contrast material is essential in CL because the highly viscous iodinated poppy-seed oil has not only diagnostic but therapeutic effects. Guidelines and randomized controlled trials are further steps towards defining the ultimate value of CL. - KEY POINTS: · PLL is a difficult-to-treat and potentially life-threatening surgical complication.. · CL has emerged as an alternative to conservative/surgical treatment of PLL.. · CL is feasible, safe, and effective in the management of PLL. · Lipiodol-based CL can be regarded as a therapeutic procedure.. · Guidelines and randomized controlled trials are further important steps.. - CITATION FORMAT: · Sommer CM, Pieper CC, Itkin M etal. Conventional Lymphangiography (CL) in the Management of Postoperative Lymphatic Leakage (PLL): A Systematic Review. Fortschr Röntgenstr 2020; 192: 1025-1035.
Gesehen am 18.01.2021
Text auf Englisch, Zusammenfassung auf Englisch und Deutsch